Fit to telework -- the changing meaning of fitness in new forms of employment. - Steward B (Advances in Physiotherapy, 2000)
Concepts of fitness are diverse and often ambiguous, and range from a lay notion of an ideal body, through medically defined, optimally functional bodily systems, to social definitions of the body's fit with employment demands. These definitions have overlapped to date. However, with the advent of new forms of computer-based work carried on outside the centralized office, conventional definitions of fitness are changing. This paper presents part of a detailed study of teleworkers' experiences of work and health, and suggests that home-based computer work changes the experience and definition of fitness to work. Teleworkers appear not to recognize conventional criteria by which symptoms are defined as illness, and so continue working when previously they would have taken sickness leave. As employee/employer relations' change, and labour markets become more uncertain, teleworkers also appear to mask illnesses. These responses result in them working longer into illness and returning sooner in convalescence. Furthermore, when illness is identified teleworkers work very long hours and take less time off work to compensate for low outputs of work. The reasons for this shift towards containment and masking are explored, and their implications for therapists are discussed in relation to public health and rehabilitation.